A “Wearable” Test for Maximum Aerobic Power: Real-Time Analysis of a 60-m Sprint Performance and Heart Rate Off-Kinetics - Storniolo, Jorge L.; Pavei, Gaspare; Minetti, Alberto E. (Frontiers in Physiology, 2017)
Maximum aerobic power (〖V ̇O〗_2peak) as an indicator of body fitness is today a very well known concept not just for athletes but also for the layman. Unfortunately, the accurate measurement of that variable has remained a complex and exhaustive laboratory procedure, which makes it inaccessible to many active people. In this paper we propose a quick estimate of it, mainly based on the heart rate off-kinetics immediately after an all-out 60-m sprint run. The design of this test took into account the recent availability of wrist wearable, heart band free, multi-sensor smart devices, which could also inertially detect the different phases of the sprint and check the distance run. 25 subjects undertook the 60-m test outdoor and a 〖V ̇O〗_2peak test on the laboratory treadmill. Running average speed, HR excursion during the sprint and the time constant (τ) of HR exponential decay in the off-kinetics were fed into a multiple regression, with measured 〖V ̇O〗_2peak as the dependent variable. Statistics revealed that within the investigated range (25-55 ml O2/(kg min)), despite a tendency to overestimate low values and underestimate high values, the three predictors confidently estimate individual 〖V ̇O〗_2peak (R2= 0.65, p<0.001). The same analysis has been performed on a 5-s averaged time course of the same measured HR off kinetics, as these are the most time resolved data for HR provided by many modern smart watches. Results indicate that despite of the substantial reduction in sample size, predicted 〖V ̇O〗_2peak still explain 59% of the variability of the measured 〖V ̇O〗_2peak.